(untitled) (Educational Knowledge, 2023)
The teaching of research methodology at the academic level presents numerous challenges, particularly in the context of training psychologists. This article analyzes the main difficulties encountered when developing a field research design, based on data analysis collected through surveys administered to fourth-year psychology students at the National University of La Plata, Argentina. The surveys were conducted in 2018 and 2022, involving a total of 280 students enrolled in the “Experimental Psychology Seminar” course, focusing on the prospective phase of research. The article also identifies proposals related to the normative, prescriptive, and reconstructive dimensions of research methodology in Psychology.